Thomas More and the genius of Utopia - Curtright, Travis (2017)
Was Thomas More a genius? This essay examines the meaning and English translation of the Latin word ingenium in the prefatory letters to the 1518 edition of Utopia. In the context of the classical oratorical tradition and its important iteration and adjustment in De copia (1512-34), the uses of ingenium indicate how humanist readers of Utopia assessed More's rhetorical abilities.
Thomas More était-il un génie? Cet article s'intéresse au sens de la traduction anglaise du mot latin ingenium dans les lettres préfaçant l'édition de 1518 de l'Utopie. Dans le contexte de la tradition oratoire classique et de ses importantes répétitions et adaptations dans le De copia (1512-34), les emplois d'ingenium peuvent nous révéler comment les lecteurs humanistes de l'Utopie ont évalué les compétences rhétoriques de More.
Keywords: art oratoire classique; classical oratory; De copia; Erasme; Erasmus; génie; Genius; ingenium; Thomas More; Utopia; Utopie